Actividad antibacteriana de extractos vegetales frente a cepas intrahospitalarias, Iquitos-Perú - Abadie y Colls., Ricardo E (2018)
The Amazon region is one of the areas with the largest biodiversity in the world, hosting several thousand species of plants, many of which are used by its people as medicinal plants. In recent years, the use of these plant resources or products has been increasing significantly, which could be due to a number of factors, among them the knowledge of their chemical composition, and the fact that at present there have been numerous pharmacological tests both in vivo and in vitro. The emergence of antibiotic-resistant strains in recent years, is creating a need for other strategies or ways to control them, as in the case of the use of plants (traditional medicine), because the active ingredients bearing. This work is intended to determine probable alternatives to combat bacterial infections of those agents antibiotic-resistant, this problem is particularly critical in developing countries, where perhaps there are no antibiotics or expensive second line, if any, price is unavailable. The study was conducted in Iquitos city, Province of Maynas, Department of Loreto. Microbiological tests were performed at Microbiology Laboratory of Research Center of Natural Resources of the Amazon (CIRNA) of the National University of the Peruvian Amazon (UNAP). The antibacterial activity of six plant extracts (Alchornea triplinervia, Annona muricata, Averrhoa carambola, Brunfelsia grandiflora, Caraipa grandifolia y Cedrela odorata) by the disk diffusion method was determined, and those that showed activity were determined Minimum Inhibitory Concentration and Minimum Bactericidal Concentration by macrodilution technique. None of the extracts were active against strains of E. coli; four extracts had activity against strains of P. aeruginosa, with Cedrela odorata and Alchornea triplinervia extracts which had greater activity against these bacteria, with MIC = 15.62 and 62.5 mg/ml, respectively; all extracts were active against strains of S. aureus, with the extract of C. odorata, A. triplinervia and Caraipa grandiflora, the most active with an MIC = 3.91 mg/ml for each. Was obtained Promising results of antibacterial activity of the extracts in study against nosocomial strains, mostly against S. aureus.